Basic biotechniques for bioprocess and bioentrepreneurship - Bhalla,Tek Chand; Bhatia, Ravi Kant; Bhatt, Arvind Kumar (Cambridge, Massachusetts Academic Press, 2023)
"Basic Biotechniques for Bioprocess and Bioentrepreneurship deals with the entire field of industrial biotechnology, starting from the basic laboratory techniques to scale-up, process development, demonstration, and finally its commercialization. The book compiles currently scattered materials on this topic and updates this information based on practical experience and requirements. The book will be an ideal source for new entrepreneurs who wish to start their own commercial units."
Includes bibliographical references and index.
Keywords: Biotechnology; Entrepreneurship; Biotechnology -- Industrial applications; Biotechnology -- Technique; New business enterprises -- Management